Insights into the gut microbiota characteristics between the organic and traditional feeding chickens based on amplicon and metagenomic sequencing - Zhang, Wenzhou; Jian, Xiaoru; Ding, Siqi; Chang, Jiamin; Ji, Shouping; Chi, Yulang (Frontiers in Microbiology, 2025)
Intestinal microorganisms play a crucial role in chicken health and production performance, especially in the research of traditional and organic feeding methods. The intestinal contents of organic and feed chickens were analyzed by 16S rRNA gene and metagenome technology. The results showed that the microbial diversity of organic chickens was significantly higher than that of the feed chickens, especially the key microorganisms, such as Enterococcus, were more abundant in organic chickens. The functional analysis of metagenome revealed the significant difference in the metabolic function of intestinal microorganisms between them. The present study provides new insights into the gut microbiota characteristics of the organic and feed chicken based on amplicon and metagenomic sequencing. Our results are helpful to fully illustrate the effects of different feeding methods on intestinal microorganisms in chickens and can offer a more scientific basis for chicken production management.